A política de assistência social realizada no município de Santarém-Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
This study aims to characterize the activities carried out by the technical team of the Municipal Department of Work and Social Assistance (SEMTRAS) of the Reference Center for Social Assistance (CRAS), identifying the main problems faced by the team and the limitations that exist to guarantee the effectiveness of social policy in the municipality of Santarém. To obtain the results and answers of this work, exploratory qualitative research was used. The data collection instrument used was a semi-structured interview, with questions, with the technical team of the Municipal Department of Labor and Social Assistance (SEMTRAS); from the Social Assistance Reference Center (CRAS) in the Nova República neighborhood. Documentary research was also used, in the consultation of several documents for the elaboration of the study, giving support for the collection of data and description of the results. We found 7 CRAS in the city of Santarém and 1 (one) in Alter do Chão. In the municipality there are two mobile teams, one that serves the plateau region and others that serve the riverside communities, they are teams that work outside the CRAS locations. The trajectory of professionals in the execution of public policy shows up with high staff turnover, often harming the continuity of actions and maintenance of them with the reality of users. The Social Assistance Reference Center (CRAS), Nova República, was implemented in 2006, 15 years ago, considered the first CRAS in Santarém, with the objective of guaranteeing access to the social rights of families in situations of vulnerability and social risk. In the municipal context, we find actions that aim to minimize traces of poverty and extreme poverty, protect the family and the individual, support children, adolescents and the elderly.
Keywords: Política; Assistência Social; SUAS; Santarém; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS